Psychoanalytic intervention with cultural differences: The categorical confusion in the relationship with the second generations of immigrants - Fusacchia, Marta; ricchiuto, serena (Quaderni di Psicologia Clinica, 2022)
In this work the authors rethink the construct of integration in connection with the problems that arise in the intervention with immigrants’ children in Italy. The encounter with cultural diversity entails an experience of alienation from one’s own culture, an experience that can be distressing if not thought of.Starting from this hypothesis, the authors explore the models of coexistence that guide the relationship between Italian institutions and families from different cultures, analyzing the function that language assumes in them. Two intervention experiences are reported, one in a school starting from the role of teacher, the other in a home educational assistance service, starting from the role of educator. Within the translation of the mandate of these contexts, there is a tendency to resolve the integration of cultural differences from an individualist perspective, placing it at the expense of the other, who is different, to be included.The encounter with the so-called second generations raises specific, interesting questions, because it evokes an ongoing cultural change and shakes that dichotomous symbolization of reality oriented by Italian/foreigner categories, thus urging a rethinking of inclusive actions. We propose the development of a psychoanalytic function based on the reading of the individual-context relationship, aimed at supporting integrative processes that recognize existing cultural differences, in order to feel them as a useful experiences, useful in producing new cultures.